EFFECT OF INFORMATION SECURITY ON THE PERFORMANCE OF NETWORKING ORGANISATION IN EBONYI STATE - Ede, Titus Eguji (EBSU Journal of Social Sciences and Humanities, 2024)
The study evaluated the effect of information security on the performance of networking organisation in Ebonyi State. The specific objectives aretto: examine the effect of access control on the profitability and evaluate the effect of security policy on the number of customers. The staff of networking organisations was used. The population of the study was 313 staff and was used due to small number. The study used the descriptive survey design. The primary source of data was the administration of questionnaire. Two hundred and seventy one (271) staff returned the questionnaire and accurately filled. Data was analyzed by mean score and standard deviation. The hypotheses were analyzed using Z - test. The findings indicated that Access control had significant positive effect on the profitability,Z(95.n = 271),6.439 < 9.902,P. < .05 and Security policy had significant positive effect on the number of customers of networking organisations Z(95.n = 271), 7.836 < 10.084,P. < .05. The study concluded that Access control and Security policy had significant positive effect on the profitability and the number of customers. The study recommended among others that the organisations should ensure Security in the organisationsto protect a building and its occupants, data and assets.